Oligodendroglioma cístico e positividade das reações para cisticercose relato de caso - Agapejev, Svetlana [UNESP]; Alves, Armando [UNESP]; Zanini, Marco Antonio [UNESP]; Ueda, Anete K. [UNESP]; Pereira, Emílio M. [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 1992)
São poucos os estudos sobre gliomas «low-grade». Os oligodendrogliomas representam de 1,3 a 10% dos tumores intracerebrais. A neurocisticercose é uma das mais graves parasitoses do SNC, com evidente polimorfismo clínico e laboratorial. O objetivo deste estudo é relatar o caso de um doente com cefaléia, perda progressiva da visão, alteração do comportamento e, provas imunológicas positivas para cisticercose no líquido cístico e cefalorra-queano. Após tentativas para tratamento da neurocisticercose, sem muito sucesso, foi submetido a craniotomia frontal para exérese de tumor cístico, que revelou tratar-se de oligodendroglioma. Discutem-se aspectos relacionados aos possíveis mecanismos para associação de neurocisticercose e oligodendroglioma.

A case of a 32-years old male patient with complaints of frontal headache progressive decrease in visual acuity, altered behaviour, and positive results of immunological tests for cysticercosis performed on the cystic and cerebrospinal fluids is presented. After several clinical and surgical proceedings, the frontal craniotomy was indicated and a multi-lobulated cystic tumor was excised. Biopsy material revealed an oligodendroglioma invading the degenerated membrane of cystic wall. Some aspects related to the possible mechanisms involved in the association cf oligodendroglioma with neurocysticercosis in the presented case are discussed. Three different types of conclusions may be reached: (1) neurocysticercosis may have acted as an oncogenetic factor for the oligodendroglioma; (2) the glycoprotein nature of the antigens of gliomas and cysticercosis and the similarity in the molecular weight range of their polypeptides may be responsible for the positivity of the reactions for cysticercosis in the cystic fluid; or (3) the association of oligodendroglioma with cysticercosis may be a simple coincidence. The present study strengthens the opinion that other pathologies should be looked for when clinical treatment of cysticercosis does not follow the expected course.
Cystic oligodendroglioma and positivity of reactions for cysticercosis: case report
Keywords: oligodendroglioma; cisticercose (neuro); oncogênese; oligodendroglioma; cysticercosis (CNS); oncogenesis